From aquatic biota to autogenous N-doping biochar—using a highly efficient nonradical dominant process for sulfamethoxazole degradation. (1st November 2022) - Xia, Wu; Song, Biao; Yi, Huan; Almatrafi, Eydhah; Yang, Yang; Fu, Yukui; Huo, Xiuqing; Qin, Fanzhi; Xiang, Ling; Zeng, Yuxi; Zeng, Guangming; Zhou, Chengyun
Abstract: Biochar has been considered as a promising environmental-friendly catalyst to activate peroxydisulfate (PDS) for contaminant degradation. In this study, a series of autogenous N-rich biochar derived from Spirulina were prepared by K2 CO3 impregnation (NPSBs). The pyrolysis temperature and the rational design of morphology by K2 CO3 had a significant influence on the performance of NPSBs to activate PDS. The NPSB-700 was capable of degrading 97.59% sulfamethoxazole (SMX) within 40 min because of the high surface area, high defect degree, and good electrical conductivity. The accelerated electron transfer and the generation of 1 O2 were elucidated to be the dominant pathways for SMX degradation. It has been proven that this is a process of reducing toxicity. Furthermore, NPSB-700 also showed excellent degradation performance to various pollutants. This study provides a facile modification strategy of Spirulina -based catalysts and deepens the comprehension of persulfate activation via nonradical oxidation. Graphical abstract: Image 1 Highlights: Autogenous N-doping biochar derived from Spirulina (NPSB-700) were fabricated. NPSB-700 was an efficient catalyst in sulfamethoxazole (SMX) degradation. The vacancies and defects, OC, and graphitic N and pyridinic N atoms acted as the possible active sites. Nonradical pathways dominated the degradation process.